Women and Economic Production: Towards Sustainable Livelihoods in Zimbabwe (International Journal of Criminology and Sociology, 2021)
Persistent drought and economic collapse in Zimbabwe have seen most, if not all, rural women shifting from the receiving end to the giving end. Rural women have since initiated several livelihood activities to make ends meet, as they are the most vulnerable whenever they are left to look after children at home. The paper aims to examine rural livelihoods and how they contribute to economic production in Ward 5 of Bikita district. A mixed design in the form of a case study was employed in this study. Systematic random sampling was used to select 40 households, which provided data for the study out of 409 households in Ward 5. The study used questionnaires and semi-structured interviews as data collecting instruments. Several livelihood activities were noted in the ward including seasonal farming, gardening, community-based and money lending and saving schemes (fushai), informal trading, and petty trading as selling thatch grass and firewood, among others. However, climate change and drought, economic crisis, lack of capital and poor soils and poor farming methods were some of the constraints faced in rural livelihoods. The paper concludes with several recommendations for eradicating rural livelihood challenges.